(untitled) (Ornitología Colombiana, 2021)
Species limits in the Andean hummingbird genus Urosticte have been in doubt for over a century, with one to three species having been recognized by different authors. The source of disagreement is the description of U. intermedia by Taczanowski in 1882 from NE Peru, a form supposedly intermediate between the Pacific- slope benjamini and the Amazonian-slope ruficrissa. Based on examination of the extant material of intermedia and distribution of all forms, we conclude that intermedia represents a mutant phenotype in a population of ruficrissa and thus has no taxonomic validity; we recommend recognition of benjamini and ruficrissa as distinct species, and further conclude that there is no basis for inclusion of benjamini in the avifauna of Peru.